Health effects and toxicological outcomes of exposure to inhalable particulate matter from urban air pollution: A mini review - Arif, Ali Talib (International Journal of Environment, Agriculture and Biotechnology, 2023)
Inhalable air pollution consists of a complex mixture of solid PM (Particulate Matter) or liquid and gaseous components originating from a myriad of natural and anthropogenic sources that cause harmful to humans, animals or plants. From the environmental aspect, air pollutants include PM, carbon monoxide, ozone, nitrogen dioxide and sulfur dioxide. Ambient levels and composition often vary greatly depending on the emission sources and meteorological conditions. There are many hazardous air pollutants such as benzene, dioxin, asbestos and metals; however, the mass of PM is one of the most widely accepted indicators of air quality monitoring and regulation. Epidemiological and toxicological studies have identified an association between elevated levels of PM in the “respirable size fraction” and adverse health outcomes in the general population. For this reason, airborne PM has recently been listed as a potentially carcinogenic agent by the International Agency for Research on Cancer (IARC) because of its heterogeneity and variation of chemical composition over space and time.